Dysfunctional risks of the internet and their overlap in the different stages of adolescence - Díaz-López, Adoración; Caba-Machado, Vanessa; Machimbarrena, Juan Manuel; Ortega-Barón, Jessica; Pérez-Rodríguez, Priscila; González-Cabrera, Joaquín (Cyberpsychology: Journal of Psychosocial Research on Cyberspace, 2026)
The use of the internet is a normative phenomenon associated with problems for younger people. The dysfunctional risks are those in which there is a problematic use of technologies that generates negative consequences. General Problematic Internet Use (GPIU) is the most prevalent, while Internet Gaming Disorder (IGD) and Online Gambling Disorder (OGD) are less prevalent, perhaps because they are Clinical problems and notably more severe. They have been widely studied separately but have hardly been examined conjointly and overlappingly. This study employs a sample with a broad age range including participants across the three stages of adolescence (early, middle, and late) and emerging adulthood. The objectives are to analyze: 1) the overall prevalence of GPIU, IGD and OGD; 2) the prevalence of GPIU, IGD and OGD according to the degree of the reported problem; 3) overlap of GPIU, IGD and OGD. These objectives will be carried out according to the variable sex and stages of adolescence. Cross-sectional and analytical study with 7,295 participants aged between 11 and 22 years. Considering risk, 13.8% of the participants had one or more risks; 11.5% presented at least one risk, 9.6% presented GPIU; 2% presented GPIU and IGD together; in only 0.1% did all three risks overlap. Girls present higher prevalence of GPIU, and boys of IGD, OGD and in all the overlaps. There is a general upward trend in middle and late adolescence versus early adolescence in these risks, which decline in emerging adulthood. These data are discussed concerning their importance in psychoeducational prevention and intervention actions.
Keywords: internet; video games; gambling; overlaps; risks; adolescence